2018
DOI: 10.1007/s10238-018-0490-9
|View full text |Cite
|
Sign up to set email alerts
|

Plasma clot formation and clot lysis to compare effects of different anticoagulation treatments on hemostasis in patients with atrial fibrillation

Abstract: The effect of direct oral anticoagulants (DOACs) on turbidimetric measurements of plasma clot formation and susceptibility to fibrinolysis may facilitate a comparison between different classes of anticoagulants in plasma samples. We obtained 424 citrate plasma samples from 226 atrial fibrillation patients on anticoagulation and 24 samples without anticoagulation serving as controls. As comparators, we measured the international normalized ratio (INR) for phenprocoumon samples (N = 166), anti-Xa for low molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…58 Additionally, it has been shown that dabigatran, rivaroxaban, and apixaban enhance fibrinolysis, but this depends on the presence of thrombomodulin in the test system. [59][60][61][62] As such, caution should be used when performing and interpreting the results from any coagulation-related test from a DOAC-treated patient. 37…”
Section: Interference Of Doac On Platelet Aggregation and Fibrinolysis Assaysmentioning
confidence: 99%
“…58 Additionally, it has been shown that dabigatran, rivaroxaban, and apixaban enhance fibrinolysis, but this depends on the presence of thrombomodulin in the test system. [59][60][61][62] As such, caution should be used when performing and interpreting the results from any coagulation-related test from a DOAC-treated patient. 37…”
Section: Interference Of Doac On Platelet Aggregation and Fibrinolysis Assaysmentioning
confidence: 99%
“…16,17 In addition, anticoagulants have been shown to delay clotting lag time and increase the efficiency of clot lysis. 11,[18][19][20][21] The effects of anticoagulants on clot structure have been previously investigated using thrombin 12,13,15,22 or tissue factor (TF), 11,14,16,17,[19][20][21]23,24 as well as TF-bearing cells 25,26 as clotting agonists. In addition, thrombus growth and fibrin distribution patterns, related to clot stability, have also been studied with TF-bearing collagen surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Direct thrombin inhibitors have also been shown to delay thrombin generation and increase clot permeability 16,17 . In addition, anticoagulants have been shown to delay clotting lag time and increase the efficiency of clot lysis 11,18‐21 …”
Section: Introductionmentioning
confidence: 99%
“…90 In one study measuring ex vivo plasma clots from patients with atrial fibrillation by turbidimetric analysis, dabigatran and factor Xa inhibitors delayed clot formation and modestly decreased clot firmness. 91 In contrast, another study scrutinizing thrombin generation and clot firmness in whole-blood and plasma by using TEG from eight heathy volunteers demonstrated that while both FXa inhibitors and dabigatran effectively prolonged thrombin generation, neither altered clot firmness. 92 These findings resembled the results from another double-blinded, placebo, randomized controlled trial (RCT) that included 35 CAD patients on DAPT with aspirin and clopidogrel.…”
Section: Direct Thrombin Inhibitor (Dabigatran)mentioning
confidence: 99%